2022
DOI: 10.3390/children9121931
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a Pedagogical Model to Increase Motivation and Decrease Disruptive Behaviour in Physical Education

Abstract: The application of gamified learning in physical education is becoming increasingly popular. The aim of this work was to compare the effects of gamification versus traditional methodology to check whether there were differences in the attitudes of the students. A quasi-experimental design study was carried out. The sample consisted of 66 students in Secondary Education. Three questionnaires, POSQ (Perception of Success), BPN (Basic Psychological Needs) and CCDEF (Disruptive Behaviour in Physical Education), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Another study, which sought to relate the use of gamification to student motivation, concluded that a physical education program based on this method improved the levels of intrinsic motivation in students compared to the control group [15] . In the same way, a study concluded that the use of the gamification method helps with the improvement of motivation and the decrease of disruptive behaviors of their students [47] .…”
Section: Discussionmentioning
confidence: 89%
“…Another study, which sought to relate the use of gamification to student motivation, concluded that a physical education program based on this method improved the levels of intrinsic motivation in students compared to the control group [15] . In the same way, a study concluded that the use of the gamification method helps with the improvement of motivation and the decrease of disruptive behaviors of their students [47] .…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, the comments made during the focus group interviews indicate that contempt and harassment were perceived right from the beginning of the sessions as attitudes that should be avoided. According to previous studies, gamification may help to prevent violent behaviours, increasing a group's cohesion (Arufe Giráldez, 2019;Dolera-Montoya et al, 2021), and could be a barrier against disruptive behaviours in the classroom (Soriano-Pascual et al, 2022). Therefore, the support for behaviours that promote respect among students and prevent contempt and harassment is probably closely related to the improvement of BPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies exist on how gamification affects students' BPNs in PE, especially in primary education. Some recent gamified experiences were found to improve the three BPNs of secondary education students (Fernandez-Rio et al, 2022;Soriano-Pascual et al, 2022;Sotos-Martínez et al, 2022). Regarding primary education, the literature is scarce, especially in PE, and the methodologies employed as well as the results are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…In general, gamification in physical education can significantly increase student engagement for several reasons. Firstly, gamification elements add a fun and exciting component to physical activities, which enhances students' intrinsic motivation to participate (Soriano-Pascual et al, 2022). Turning tasks into challenges and competitions creates a competitive and stimulating environment that fosters student engagement (Aleksic-Maslac et al, 2017).…”
Section: Introductionmentioning
confidence: 99%